CO2 Corrosion of Low Carbon Steel Under the Joint Effects of Time-Temperature-Salt Concentration - Li, Shengxi; Zeng, Zhipeng; Harris, Michael A.; Sánchez, Lizeth J.; Cong, Hongbo (Frontiers in Materials, 2019)
The time-dependent effect of temperature and salt (NaCl) concentration on the corrosion behavior of carbon steel in CO2-saturated environments were explored using various electrochemical techniques coupled with XRD, Raman spectroscopy and SEM/FIB examinations. At constant salt level, corrosion rate increased and stabilized when temperature was below 60 °C. When temperature was higher than 60 °C, corrosion rate firstly increased, reached an apex, and then started decreasing continuously. The magnitude of the decrease is inversely proportionally to the salt concentration, which is then attributed to the microstructure of dual-layer FeCO3 scale. Polarization experiments indicate the anodic process is more affected by salt concentration than temperature while the opposite is true for the cathodic kinetics. Although chloride is not detected in the corrosion scale, it is regarded to have significant influence on the nucleation and growth of FeCO3 and therefore the properties (e.g., thickness and compactness) of the corrosion scales. Lastly, a mechanism is proposed for the evolution of corrosion scales on carbon steel in CO2 saturated environment as a function of temperature and salt concentration.